30.9k views
5 votes
Fill in the missing statements and reasons in this proof. Number your reasons 1 through 5 as they would be shown in the chart below.

Given: m∠LOM = m∠JKI;
m∠MON = m∠IKH
Prove: m∠LON = m∠HKJ

Fill in the missing statements and reasons in this proof. Number your reasons 1 through-example-1
User WhiteSkar
by
5.6k points

1 Answer

5 votes

Answer:

m∠LON = m∠HKJ

Explanation:

. m∠LOM = m∠JKI; m∠MON = m∠IKH 1.

2. m∠LOM + m∠MON = m∠JKI + 2.

m∠MON

3. m∠LOM + m∠MON = m∠JKI + 3.

m∠IKH

4. m∠LOM + m∠MON = m∠LON; 4.

m∠JKI + m∠IKH = m∠HKJ

5. m∠LON = m∠HKJ 5.

User InterstellarX
by
5.1k points